The Informational Role of Product Trade‐Ins for Pricing Durable Goods1. (December 2015) - Kwon, Ohjin; Dukes, Anthony J.; Siddarth, S.; Silva‐Risso, Jorge M.
Abstract : This research theorizes that sellers of durable goods can utilize inferences about the buyer's willingness to pay based not only on her decision to trade in the old good but also on its characteristics. We find empirical support for this theory using transaction data for new car purchases. The results support the notion that dealers infer a higher willingness to pay and charge higher prices to consumers who trade in a used vehicle than to those who do not. We also find that dealers charge even higher prices to those consumers who trade in used cars that are similar to the new one.